Moderate to Severe Anemia Is Associated with Poor Functional Outcome in Acute Stroke Patients Treated with Mechanical Thrombectomy - Akpinar, Cetin Kursad; Gurkas, Erdem; Aytac, Emrah (Karger, 2018)
Background: Anemia will negatively affect cerebral collaterals and penumbra. Eventually, it may cause worse clinical outcomes and even increase mortality rates in stroke patients. Anemia has recently been suggested to be an independent risk factor for ischemic stroke. Therefore, we aimed to investigate the effects of the presence of anemia on clinical outcomes in ischemic stroke patients undergoing mechanical thrombectomy. Methods: This was a retrospective study involving the prospectively and consecutively collected data of 90 adult patients between January 2015 and August 2016. Hemoglobin (Hb) cutoff levels were accepted as 12 g/dL for women and 13 g/dL for men. Patients having anemia were further divided into three subgroups as severe anemia (Hb < 8 g/dL for both genders), moderate anemia (Hb < 10 g/dL for both genders), and mild anemia (Hb < 13 g/dL for men and Hb < 12 g/dL for women). Results: Forty of the subjects (44.4%) had anemia. Moderate anemia was detected in 14 out of 90 patients (15.5%) and severe anemia was found in only four of them (4.4%). Poor functional outcome (mRS 3-6) was similar in both anemic and non-anemic patients (37.5% vs. 38%, respectively, p = 0.08), but poor functional outcome was found to be statistically significant with severe anemic group (Hb < 8 mg/dL) (p = 0.003). In multiple logistic regression analysis, moderate and severe anemia has been found to increase the mortality (p = 0.032). Conclusions: Our study demonstrated a poor functional outcome only in moderate to severe anemic patients. Clinicians should keep in mind the negative effect of moderate to severe anemia in the clinical course of acute stroke patients treated with mechanical thrombectomy. (c) 2017 S. Karger AG, Basel
Keywords: Acute stroke; Functional outcome; Mechanical thrombectomy; Anemia